1989
DOI: 10.1016/0731-7085(89)80160-8
|View full text |Cite
|
Sign up to set email alerts
|

Analytical applications of circular dichroism

Abstract: The goal of the present research has been to develop a selective analytical detection procedure for the easy identification and assay of drugs and related substances present in complex mixtures, without a chromatographic separation step or other work up. The detector of choice is circular dichroism (CD) spectropolarimetry which has the appropriate balance between degree of analytical selectivity and breadth of application. Applications that are described are selected from work carried out in the context of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…The near-UV CD spectrum can be sensitive to small changes in tertiary structure due to protein-protein interactions and ⁄ or changes in solvent conditions (15). The signal strength in the near-UV CD region is much weaker than that in the far-UV CD region.…”
Section: Protein Analysesmentioning
confidence: 99%
“…The near-UV CD spectrum can be sensitive to small changes in tertiary structure due to protein-protein interactions and ⁄ or changes in solvent conditions (15). The signal strength in the near-UV CD region is much weaker than that in the far-UV CD region.…”
Section: Protein Analysesmentioning
confidence: 99%
“…This is why it is important that determination of AMP species should be carried out by methods that are capable of providing information on the enantiomeric purity and chirality. However, the amphetamine molecule has not, according to our knowledge, been chirally examined, except by electronic circular dichroism (CD), which showed that the AMP-CD signal was too weak to be conclusive [7]. Therefore, the following study can be considered as the first of its kind on the AMP molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pretreatment of biological samples usually requires specific polar solvents incompatible with normal phase . Usually, the complexity of an enantioseparation problem can be simplified by the use of circular dichroism detectors .…”
Section: Introductionmentioning
confidence: 99%